Utilization potential of rangeland shrubs of Bundelkhand: Areview - Singh, Kaushal; Gupta, Garima; Dobriyal, Manmohan J (Indian Journal of Agroforestry, 2022)
Rangelands in India are spread over 12.15 million ha. More than 40% of thelarge population of livestock still depend upon grazing in the rangelands / pastures on highaltitudes, desert, semi arid/arid areas. The Bundelkhand region in central India is a typicalrainfed semi-arid region. This area has degraded, undulated rocky land and constraints inarable farming, and mainly supports the growth of shrub vegetation diversity. The integrationand augmentation of promising shrubs to rangeland in arid/semi-arid conditions can playimportant role in sustaining the rainfed and fragile ecosystem of Bundelkhand ecologically andeconomically. The woody perennials provides small timber, food, fodder, fuel wood, tan, dyes,fiber , ethno-medicine, live fences, windbreak, browsing reserves, fodder bank and improvedfellow for various benefits. The prominent shrubs like Ziziphus oenoplea, Z. nummularia,Grewia asiatica, Opuntia dillenii, Capparis decidua, Carissa spinarum for food; Grewiaflavescence, G. asiatica, Helicteres isora, Vitex nigundo, Securinega virosa and Ehratia asperafor fodder and Commiphora wightii, Helecteris isora and Barleria prionitis for medicines arefew examples to mention. Shrubs are utilised for variety of purposes in Bundelkhand and amajor bioresource for the livelihood options. Thus, shrubs need to be promoted for reducingthe pressure on natural forest and to augment the green cover in the tropics of arid/semi-arid visa vis increase resource base outside the forests for local population. Due to wide adaptationsthe shrubs have the ability to improve and reclaim the degraded wasteland to cope with thefuture challenges of global climate change. Sustainable scientific management and utilisationof shrub diversity is urgently needed for integrated rangeland development in Bundelkhandregion. The paper reviewed the existing information & literature with analysis for theimportance, preservation and management of rangeland shrubs in the semi-arid tropics ofBundelkhand.